An observational report of universal GeneXpert testing of inpatients with diagnosed or presumptive TB in the Philippines - Thi, AM; Lee, N; Parris, V; Marin, FP; Roy, L; Calapis, RW; Ariyoshi, K; Parry, CM; Cox, SE (Oxford University Press, 2020)
BACKGROUND: The Philippines is a high TB and multidrug-resistant TB burden country. Although the scale-up of GeneXpert testing is occurring, the benefits of universal Xpert-Mycobacterium tuberculosis/ rifampicin (MTB/RIF) testing in inpatients have not been documented.